Assessing the impact of e-government on control of corruption and government effectiveness: Developed and developing countries - Mahmoud, Nourhan B; Hamed, Essam H; Dwidar, Mohamed S (Asian Economic and Financial Review, 2025)
This study seeks to investigate the relationship between e-government, fiscal transparency, and corruption across two distinct categories of developed and developing nations. Data were collected from reliable secondary sources spanning the period from 2003 to 2022. The study also integrated additional factors that may influence fiscal transparency and corruption, including budget components (tax revenues and expenses), population density, and economic freedom. To analyze the data, panel data econometric techniques were employed. The results revealed that e-government had a positive and statistically significant effect on controlling corruption and improving government effectiveness in developing countries. In contrast, it exhibited a negative and significant impact on corruption control and government effectiveness in developed countries. The robustness of these findings was confirmed through sensitivity analysis. Overall, the study concluded that e-government plays a crucial role in reducing corruption and enhancing government effectiveness in developing nations. However, in developed countries, it appears to have a counterproductive effect, potentially due to emerging risks in the ICT sector, such as cybercrime, online bribery, and digital fraud, which create new avenues for corruption. This study underscores the importance of implementing e-governance systems and fostering a transparent and accountable environment to mitigate corruption effectively.